2019
DOI: 10.1002/lom3.10326
|View full text |Cite
|
Sign up to set email alerts
|

Robotic mapping of mixing and dispersion of augmented surface water in a drought frequent reservoir

Abstract: The spatial and temporal evolution of an introduced dye tracer in a small reservoir was observed using a robotic autonomous underwater vehicle (AUV), providing quantifiable data of the convective processes which drive transport and mixing. The tracer served as a surrogate for advanced treated water that has been proposed to be introduced into a reservoir as part of an overall system for efficient water reclamation, a critical management tool for addressing water issues facing the southwest. While emergent auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 41 publications
3
7
0
1
Order By: Relevance
“…This delay is modulated by τ ini (Sect. 4.2) and consistent with previous studies where the onset of TS was observed at night (Monismith et al, 1990;James et al, 1994;Fer et al, 2002b;Pálmarsson and Schladow, 2008) or in the morning (Rogowski et al, 2019;Sturman et al, 1999). t is a good estimate for the onset time when the water column is initially mixed ( mix = 0).…”
Section: Effects Of the Forcing Conditions On The Flushing Periodsupporting
confidence: 91%
See 4 more Smart Citations
“…This delay is modulated by τ ini (Sect. 4.2) and consistent with previous studies where the onset of TS was observed at night (Monismith et al, 1990;James et al, 1994;Fer et al, 2002b;Pálmarsson and Schladow, 2008) or in the morning (Rogowski et al, 2019;Sturman et al, 1999). t is a good estimate for the onset time when the water column is initially mixed ( mix = 0).…”
Section: Effects Of the Forcing Conditions On The Flushing Periodsupporting
confidence: 91%
“…The increase of discharge with depth was reported in Lake Geneva by Fer et al (2002b). Values of TS thickness and discharge can be one order of magnitude larger in deeper lakes than Rotsee (Thorpe et al, 1999;Fer et al, 2002a;Rogowski et al, 2019).…”
Section: Practical Recommendations To Predict and Measure Thermal Siphons In Other Lakesmentioning
confidence: 83%
See 3 more Smart Citations